ANALISIS PENENTUAN HARGA JUAL JASA KAMAR PADA HOTEL PLAZA KUBRA KENDARI - Nurlyan, Nurlyan (JURNAL AKUNTANSI, 2016)
This study aimed to analyze the determination of the selling price of room service in the hotel plaza kubra kendari. Primary data in this study were obtained directly from the hotel plaza kubra kendari form of reports room occupancy rate and the list of operating expenses incurred during the year 2014. The method of analysis is descriptive analysis using cost plus pricing method.This study showed that the operational costs incurred plaza kubra hotel kendari greater than occupancy rates so that the expenses incurred are not comparable with the income from hotel occupancy. The results indicate that if the hotel wants to achieve the advantage of taking into account the fixed and variabel operating costs in determining the hotel room rates, by using the method of full costing and variable costing so all the operational costs can be covered so that the hotel can reach advantage.Â Â Keywords: selling price, cost plus pricing, full costing, variable costing